Therapeutic interventions in Australian primary care, youth mental health settings for young people with borderline personality disorder or borderline traits - O’Dwyer, Nikki (Borderline Personal Disord Emot Dysregul, 2020)
BACKGROUND: This study aimed to investigate what therapeutic interventions were being applied by clinicians working with young people with a diagnosis of Borderline Personality Disorder or borderline traits in Australian primary mental health care settings. Given the current lack of evidence-based guidelines for treatment with this client population, investigating what is being implemented is needed. The study also aimed to determine whether the interventions clinicians are using are effective in reducing distress and increasing functioning for these clients. METHODS: Participant data came from the national minimum data set for headspace youth mental health centers across Australia. Young people’s data were included in the study if the young person was diagnosed with Borderline Personality Disorder or borderline traits during their first episode of care (N = 701). Clinician data that indicated the type of intervention used at each client session and outcome measures routinely captured were analyzed to determine interventions used and outcomes achieved. RESULTS: Results demonstrated that CBT was the most frequently used modality of intervention followed by supportive counselling and IPT, but that most clients received a variety of intervention types. There were no or only weak relationships between changes in outcomes and the amount of any type of intervention that was provided. No significant relationship was found with the amount of CBT a client received and changes in symptoms or functioning, despite being the most commonly employed modality. CONCLUSIONS: The study highlights the need for evidence-based treatment guidelines for early intervention in young people with borderline personality disorder traits.